Preliminary morphological characterization of injectable gels for aesthetic medicine applications - Recuero Pradillo, María; Tejero-García, Paloma; Mota Antigua, Sheila Karina; Ortega Zamorano, Marta; Coca Menchero, Santiago; Flores Sáenz, Manuel (Aesthetic Medicine, 2025)
Background: Injectable gels used in aesthetic medicine for skin rejuvenation are known collectively as fillers. These gels are employed for wrinkle correction, volume restoration, and facial enhancement with some formulations predominantly providing bio-stimulating and revitalizing effects. Aim: This study aimed to analyze and compare the microscopic structure of various injectable gels. Materials and Methods: Ten products were examined, including cross-linked and non-cross-linked hyaluronic acid (HA), agarose gel, calcium hydroxyapatite combined with HA, and formulations containing collagen precursors. Smears were prepared on glass slides, air-dried, stained with Diff-Quick, and observed under optical microscopy. Results: Each material exhibited a distinct and reproducible microscopic morphology corresponding to its composition. Discussion: Microscopic analysis of injectable gels can help identify and categorize products based on their structural characteristics. This tool may assist in the identification of undocumented materials in cases of adverse reactions through fine-needle aspiration (FNA) and smear analysis. Conclusions: Morphological analysis may serve as a valuable framework to understanding the potential behavior and integration of gels within biological tissues. Greater attention to microscopic studies of injectable gels may enhance safety, efficacy, and complication management in aesthetic procedures.